Analisis Faktor-Faktor Yang Mempengaruhi Belanja Online Pada Mahasiswa Universitas Malikussaleh - Asy’ari Asy’ari; Naufal Bachri (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2020)
This study aims to determine the influence of internet technology knowledge, consumer trust, website/application quality, and product quality with online shopping decisions for fashion products among students of Malikussaleh University. This study uses primary data obtained by distributing questionnaires to 150 respondents, selected using Purposive sampling method. The data analysis method used is multiple linear regression analysis. The results of the study partially show that internet technology knowledge (X1), consumer trust (X2), website/application quality (X3), and product quality (X4) significantly influence online shopping decisions for fashion products on Malikussaleh University students. Simultaneously, internet technology knowledge (X1), consumer trust (X2), product/application quality (X3), and product quality (X4) significantlyinfluence online shopping decisions for fashion products on Malikussaleh University students. Keywords: Internet Technology Knowledge, Consumer Trust, Website/Application Quality, Product Quality